The economic spillover of South Sumatera toward economic of Southern Sumatera Provinces in Indonesia - Fitri Kurniasih; Taufiq Marwa; Saadah Yuliana; Abdul Bashir (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study to investigation effect of hinterland government expenditure each region, Gross Regional Domestic Product (GRDP), investment, consumer price index, and the road length of South Sumatera province toward the GRDP of other provinces in Southern Sumatera such as Jambi, Lampung, Bengkulu, and Bangka-Belitung Island. The data use secondary data during 1986-2015, data source from the Central Bureau of Statistics, Directorate General of Regional Fiscal Balance, and Indonesia Investment Coordinating Board. The analysis uses multiple regressions with Ordinary Least Square (OLS) method. The results showed that the economic spillover of South Sumatera consisting of gross domestic product, investment, consumer price index and the road length caused spread effects to Jambi, Lampung, Bengkulu, and Bangka Belitung with positive values except for Bangka Belitung whose consumer price index was negative.